2012
DOI: 10.3390/app2010114
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Fluorinated β-Nitrostyrenes as Antimicrobial Agents

Abstract: Abstract:The effect of variously fluorine-substituted β-methyl-β-nitrostyrenes on their antimicrobial activity was investigated. Their efficacy was determined by minimum inhibition concentration (MIC) in cultures of Gram positive and Gram negative bacteria and a fungus. Highest activity against the Gram negative bacterium, E.coli, was achieved with 4-fluorine-aryl substituted β-methyl-β-nitrostyrenes, while most compounds gave excellent results against gram positive bacteria. Importantly, the addition of the β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
2
17
1
Order By: Relevance
“…This compound has been evaluated in different assays, and the results in Table 3 are from an assay in which I was evaluated against 4-fluoro-β-nitrostyrene (without the β-methyl group), which showed that I was much better than 4-fluoro-β-nitrostyrene and also A-1. In all of our work, we have found this to be the case (see [12,13]). Table 1 shows the MICs in μg mL −1 of β-nitrostyrene analogues tested against four strains of bacteria and a fungus.…”
Section: Analysis Of Assayssupporting
confidence: 51%
See 3 more Smart Citations
“…This compound has been evaluated in different assays, and the results in Table 3 are from an assay in which I was evaluated against 4-fluoro-β-nitrostyrene (without the β-methyl group), which showed that I was much better than 4-fluoro-β-nitrostyrene and also A-1. In all of our work, we have found this to be the case (see [12,13]). Table 1 shows the MICs in μg mL −1 of β-nitrostyrene analogues tested against four strains of bacteria and a fungus.…”
Section: Analysis Of Assayssupporting
confidence: 51%
“…Three assays, as previously described [12,13], were used to determine the antibacterial efficacy of the β-nitrostyrenes by their activity against a panel of 4 bacteria and a fungus (Candida albicans). The results appear as the minimum inhibitory concentration (MIC) for each compound and are presented in the Tables 1 and 2 The three assays were performed as follows: Assay 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(11,12) This approach does not require medication, and hence, does not generate drug resistance. (13)(14)(15)(16) Because this sterilization method is effective for treating antibiotic-resistant strains, it has been receiving increasing attention. (17,18) PDI uses a specific-wavelength LED or laser irradiation on a photosensitizer (PS).…”
Section: Introductionmentioning
confidence: 99%